Phenotypic alterations in immune cells and their association with toxicities in postoperative endometrial cancer patients undergoing brachytherapy - Sun, Naiping; Liu, Jianting; Dong, Zhulin; Suo, Ruixin; Ren, Junli (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the phenotypic alterations in peripheral blood immune cells, especially natural killer (NK) cells, natural killer T (NKT) cells, total B cells, total T cells and their subsets, in postoperative patients with intermediate-risk endometrial cancer undergoing brachytherapy, and explores their association with adverse reactions.MethodsA cohort of ninety-two patients, who received brachytherapy (5.0 Gy per fraction, 6 fractions) at Shanxi Cancer Hospital from January 2022 to November 2024, was included in this study. Immune cell subsets, including CD45+CD3-CD16+CD56+ NK cells, CD3+CD56+ NKT cells, CD45+CD3-CD19+ B cells, CD3+CD8+ T cells, CD3+CD4+ CD4+ helper T cells, CD3+CD8+ Cytotoxic T cells, CD45+CD4-CD25HICD127LO Regulatory T cells, were quantified using flow cytometry pre-, during, and post- treatment. Various statistical methods were applied to analyze these phenotypic changes and the chi-square test was employed to explore their association with toxicities.ResultsCompared to pre-treatment levels, NK cells and NKT cells increased significantly during and post-treatment (P<0.001, P=0.003), while B cells decreased significantly(P<0.001). No notable alterations were observed in the counts of total T cells and their subsets throughout the treatment process (P>0.05). Brachytherapy caused mild side effects, with no toxicities of grade II or higher observed. The incidence of acute radiation proctitis was significantly higher in the group with elevated NK cell levels compared to the non-elevated group (31.9% vs. 8.7%, P=0.028). The incidence of radiation proctitis, cystitis, and vaginitis did not differ significantly among the other groups (P>0.05).ConclusionBrachytherapy enhances innate immune activation through the upregulation of NK/NKT cells, potentially correlating with the development of acute proctitis. These findings highlight immune modulation as a prospective biomarker for managing radiotherapy-induced toxicity.